Reorientando los lentes para una historia de la teoría del arte en Cuba. ¿Pensamiento cultural en Latinoamérica? - Arencibia Coloma, Yaneidys (2024)
The purpose of this article is to investigate the spaces in which emerges, consolidates and socializes the Cultural Thought of one of the most notable intellectuals of the first half of the Cuban twentieth century. It uses the methodological resources of the New Sociology of Scientific Knowledge, from a critical perspective, to examine the life and work of Jorge Mañach (1898-1961), to corroborate this Cultural Thought’s place as scientific knowledge about art and its contribution to cultural studies within the Latin American epistemic horizon. At the same time, the contingent circumstances that allowed its legitimacy are assessed. In order to visualize Jorge Mañach's cultural thought, special consideration is given not only to the analysis of his most representative theoretical texts, but also to his relationship with the cultural institutions and intellectual initiatives to which he was linked.